The Relationship Between High School Sophomores' Purpose Orientations and Their Postsecondary Completion a Decade Later. Issue 1 (11th January 2021) - Sharma, Gitima; Kim, Jungnam; Bernal-Arevalo, Katherine
This study explored the relationship between high school sophomores' purpose orientations and their postsecondary completion a decade later by examining the data from the Educational Longitudinal Study of 2002. Among four types of purpose (career, interpersonal, altruistic, and self-oriented), career and interpersonal purpose orientations were positively related to postsecondary completion. We discuss implications for school counseling and future research.